Pengembangan Media Pembelajaran Berbantuan Aplikasi Geogebra Berbasis Model Discovery Learning di Kelas V Sekolah Dasar - Salsabiila, Anisa; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
Elementary schools in the city of Padang both public and private have facilities and infrastructure that support but from the observation shown that the use of the technological infrastructure has not been optimized. This research aims to produce GeoGebra-based learning media in Grade V Elementary School that is valid, practical, and effective. The type of research used is Research and Development Research with ADDIE (analysis, design, development, implementation and evaluation) model. Data analysis techniques used are; validity, practicality, and effectiveness data analysis. Validation instrument of Learning media is in the form of validation by 3 experts, namely media experts, linguists and experts on media-related materials produced. Media practicality instruments in the form of teacher response questionnaires and student response questionnaires related to the developed media. Effectiveness instruments in the form of learning evaluation questions given to learners to determine whether the media used is effective. Based on the analysis that has been done, GeoGebra-Based Learning media developed with ADDIE model is valid, practical and effective use in elementary school in learning mathematics material volume of space and the relationship of the cube to the cube root